2010
DOI: 10.1021/jm100230k
|View full text |Cite
|
Sign up to set email alerts
|

Online Fluorescence Enhancement Assay for the Acetylcholine Binding Protein with Parallel Mass Spectrometric Identification

Abstract: The acetylcholine binding protein (AChBP) is considered an analogue for the ligand-binding domain of neuronal nicotinic acetylcholine receptors (nAChRs). Its stability and solubility in aqueous buffer allowed the development of an online bioaffinity analysis system. For this, a tracer ligand which displays enhanced fluorescence in the binding pocket of AChBP was identified from a concise series of synthetic benzylidene anabaseines. Evaluation and optimization of the bioaffinity assay was performed in a conveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 21 publications
2
56
0
Order By: Relevance
“…This phenomenon of excessive band broadening observed for high concentrations of ligand injected is common when working with on-line and at-line reconstructed bioassay chromatograms. 13 ACh showed a strong and repeatable signal in the Ca 2+ -flux assay when relatively high concentrations were injected. ACh also elicited a Ca 2+ -signal in the nanomolar range (500 nM injected concentration, about 45 nM in the assay), which indicated that the signals might be caused not only by signaling via the α7-nAChR (pKi of ACh is 5.1 ± 0.1 for the α7-nAChR 30 ).…”
Section: At-line Cellular Screening Setup In Agonist Assay Formatmentioning
confidence: 90%
See 1 more Smart Citation
“…This phenomenon of excessive band broadening observed for high concentrations of ligand injected is common when working with on-line and at-line reconstructed bioassay chromatograms. 13 ACh showed a strong and repeatable signal in the Ca 2+ -flux assay when relatively high concentrations were injected. ACh also elicited a Ca 2+ -signal in the nanomolar range (500 nM injected concentration, about 45 nM in the assay), which indicated that the signals might be caused not only by signaling via the α7-nAChR (pKi of ACh is 5.1 ± 0.1 for the α7-nAChR 30 ).…”
Section: At-line Cellular Screening Setup In Agonist Assay Formatmentioning
confidence: 90%
“…[11][12][13][14] Most importantly, functional bioassays can also be implemented in these screening methodologies. 9 A functional bioassay gives the advantage of not only measuring binding affinity of a ligand, but also measuring functional activity and allowing distinction between, for example, agonism, antagonism, and allosteric modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Expression and purification from the medium is described by Celie et al 15 the assay is based on the competition of ligands with the tracer ligand daHBa, which has an increased fluorescence yield in the active site of aChBP. 10 the following triS/PBS buffer was used: 1 mM KH 2 Po 4 , 3 mM na 2 HPo 4 , 0.16 mM naCl, and 20 mM trizma-base at pH 7.5 with 400 mg/l EliSa Br. For operation of the superloops (10 ml in-house-built superloops) delivering the biochemical assay constituents (aChBP and tracer ligand daHBa), two Shimadzu lC10advp pumps (50 µl/min) were used, resulting in continuous delivery of 6.6 nM aChBP (lower superloop) and 150 nM daHBa (upper superloop) to an inverted y-shaped mixing piece prior to coupling to the spotter heart.…”
Section: Biochemical Assaymentioning
confidence: 99%
“…Evaluation, validation, and actual high-resolution bioactivity profiling of pure compounds and mixtures on the AChBP aided by the nanofractionation spotter technology the reason for using the aChBP biochemical assay format in this offline mode rather than the recently described online format 10 is the capability of the offline format to identify compounds with slow binding kinetics, which require long incubation times for binding equilibrium to be reached. Efficient measurement of these types of compounds, such as α-bungarotoxin, 17 a peptidic antagonist of the α7 naChr with a molecular weight of ˜8000 da, is not possible with the online format.…”
Section: Bmentioning
confidence: 99%
“…After its crystal structure was published [19], it has become a model for nAChRs to efficiently screen compound libraries for potential ligands and for structure based synthetic approaches in medicinal chemistry [20]. The nAChR family is intensively studied in relation to its potential as pharmaceutical target against epilepsy, Alzheimer's disease, pain relief, Parkinson's disease, anxiety and cognitive and attention deficits [17,18,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%